Dynamic Hypothesis of Performance Model for Academic Staff - Sapiri, Hasimah; Zainal Abidin, Nor Haslinda; Abdul Halim, Tisya Farida (Institute of Research Engineers and Doctors, 2014)
This article presents the development of a dynamic hypothesis for academics staff performance in higher education institution. The performance of academic staff focus on the three interrelated key indicators. They are research, publication and supervision. Then, the hypothetical framework portraying the main interacting variables and its relationship in influencing academic staff performance was developed. It highlights the feedback process between structural, process and the performance factors. The conceptual framework was designed as a preliminary step towards the simulation model development. The dynamics hypothesis enables the researcher to gain insight into the complexity of evaluating academics staff performance